Pengaruh Brand Image Dan Brand Trust Terhadap Loyalitas Pelanggan Pada Toko Otomotif Putra Jaya Labuhanbatu Selatan - Sari, Monika (Jurnal Manajemen Akuntansi (JUMSI), 2021)
We are a company engaged in the procurement of goods and services industry. The data set was carried out by distributing questionnaires and distributed to 50 research samples, namely Putra jaya automotive store consumers. Data analysis in this study using the help of SPSS version 20. Multiple linear regression analysis, multiple linear regression analysis, multiple linear regression analysis, multiple linear regression analysis, and multiple regression analysis. The results showed that the brand image has a positive effect on customer loyalty it can be seen from the value of t count>t table (3,523 > 2,010), brand image has a positive effect on customer loyalty it can be seen from the value of t count > t table (5,538>2,010), brand image and brand trust F table (48,918 > 3,20).